2011
DOI: 10.4148/1051-0834.1173
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Legislation: The Presence of California Proposition 2 on YouTube

Abstract: Animal rights movements continue to be a threat to the livestock industry in the United States. In 2008 California voters passed a proposition (2) which outlawed the use of battery cages for laying hens, gestation crates for sows, and veal crates for veal calves by 2015. Similar measures have previously been passed in Florida, Arizona, Colorado, and Oregon. As animal rights activists continue to pressure the livestock industry, it is important to look at their information outlets, especially those targeted tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 8 publications
(5 reference statements)
1
15
0
Order By: Relevance
“…Information must be framed in a way to give consumers a positive mental image and leave them with a feel-good experience. Additionally, Goodwin and Rhoades (2011) concluded that consumers who felt emotionally connected with an advertisement were more likely to connect with the product. This study showed personal relevancy or emotional appeals may be used to connect consumers to their products.…”
Section: Framingmentioning
confidence: 99%
“…Information must be framed in a way to give consumers a positive mental image and leave them with a feel-good experience. Additionally, Goodwin and Rhoades (2011) concluded that consumers who felt emotionally connected with an advertisement were more likely to connect with the product. This study showed personal relevancy or emotional appeals may be used to connect consumers to their products.…”
Section: Framingmentioning
confidence: 99%
“…Goodwin and Rhoades (2011) looked at the presence of California Proposition 2 on YouTube. Proposition 2 was a ballot initiative that passed in 2008 that "outlawed the use of battery cages for laying hens, gestation crates for sows, and veal crates for veal calves by 2015" (Goodwin & Rhoades, 2011, p. 22).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers determined what message appeals were used to increase viewers' support for the legislation and found that emotional appeals were used in a majority of the videos. They encouraged others to replicate the study with other issues posted on YouTube and extend the research to other social networking sites (Goodwin & Rhoades, 2011). In addition, Rhoades and Ellis (2010) studied how food safety was framed on YouTube videos and found several authors were posting multiple videos, concluding that "establishing a presence and publishing multiple videos can help the reach of a communication campaign and establish your credibility with the social network found on YouTube" (Rhoades & Ellis, 2010, p. 172).…”
Section: Introductionmentioning
confidence: 99%
“…Lundy and colleagues noted a diverse group of individuals attempt to communicate scientific topics to the public, including scientists, public information officers, and the media. One group specifically equipped to provide the public with agricultural information is agricultural communicators, and this group must be careful to create more convincing arguments that combat anti-agriculture campaigns that sway a public with a weak understanding of agriculture in the opposite direction (Goodwin & Rhoades, 2011). Research also noted a need for agricultural commodities to be more concerned with depicting reality than being entertaining during advertising efforts (Specht & Buck, 2014).…”
Section: A Version Of This Manuscript Was Presented At the 2015 Assocmentioning
confidence: 99%
“…Consumer education should become a higher priority for the poultry production integrators in Arkansas, such as Tyson Foods, Inc.; OK Foods, Inc.; Simmons Foods, Inc.; Cobb-Vantress, Inc.; and George's, Inc. Communicators in agricultural based organizations should be careful to depict reality while engaging in marketing efforts, as well as work to create convincing arguments to combat other campaigns that may misrepresent agriculture to the public (Goodwin & Rhoades, 2011;Specht & Buck, 2014). Marketing efforts should be directed at women; whereas, previous research noted they are the primary consumers for groceries (Dholakia, 1999).…”
Section: Recommendations and Implicationsmentioning
confidence: 99%